Faktor yang Mempengaruhi Nilai Perusahaan Pada Sektor Consumer Goods Industry - Nixon Natanael Alexander; Hendra Hendra (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The purpose of this research is to determine some of the factors that could affect the value of the company. The independent variables used in this research are managerial ownership, institutional ownership, capital structure, profitability, company growth, company size, and dividend policy. The object of this research is Consumer Goods Industry sector that are listed on the Indonesia Stock Exchange (IDX) in 2016-2020. This research used 40 samples and the research method used was purposive sampling method. The data analysis method used is descriptive statistics and regression panel with a FEM model to testing all hypothesis. Based on the results of this study, it was concluded that the profitability and growth of the company affect the value of the company. Profitability has a positive effect to firm value because the company profit reflects a good performance of company so the investor sees this as a positive signal. Growth has a negative effect because investor sees that company will retain the dividend for financing the new opportunity. Meanwhile, managerial ownership, institutional ownership, capital structure, company size, and dividend policy have no effect on firm value.